Evaluating tools for the spatial management of fisheries. Issue 6 (24th July 2018) - Canty, Steven W. J.; Truelove, Nathan K.; Preziosi, Richard F.; Chenery, Simon; Horstwood, Matthew A. S.; Box, Stephen J.
Abstract: The ability to define the spatial dynamics of fish stocks is critical to fisheries management. Combating illegal, unreported and unregulated fishing and the regulation of area‐based management through physical patrols and port side controls are growing areas of management attention. Augmenting the existing approaches to fisheries management with forensic techniques has the potential to increase compliance and enforcement success rates. We tested the accuracy of three techniques (genotyping, otolith microchemistry and morphometrics) that can be used to identify geographic origin. We used fish caught from three fishing grounds, separated by a minimum of 5 km and a maximum of 60 km, to test the accuracy of these approaches at relatively small spatial scales. Using nearest‐neighbour analyses, morphometric analysis was the most accurate (79.5%) in assigning individual fish to their fishing ground of origin. Neither otolith microchemistry (54.0%) or genetic analyses (52.4%) had sufficient accuracy at the spatial scales we examined. Synthesis and applications . The combination of accuracy and minimal resource requirements make morphometric analysis a promising tool for assessing compliance with area‐based fishing restrictions at the scale of kilometres. Furthermore, this approach has promising application, in small‐scale fisheries through to community‐based management approaches where technical and financial resources are limited. Abstract : The combination of accuracy and minimal resource requirements make morphometric analysis a promising tool for assessing compliance with area‐based fishing restrictions at the scale of kilometres. Furthermore, this approach has promising application, in small‐scale fisheries through to community‐based management approaches where technical and financial resources are limited.